The Implementation of Video Animation "Best Friend in the World" in Pronunciation Learning - Anisa, Anisa; Hidayah, Linta Wafdan; Bahruddin, Dinar Vincy Yunitaka (JET ADI BUANA, 2025)
Pronunciation is the important element in English communication, but many students have difficulty in learning pronunciation, one of the reasons is due to the lack of learning media that attracts students. The objective of this research is to find the steps of the implementation of the video animation “Best Friend in the World” in learning pronunciation and challenges. This research was conducted in seventh grade at SMP Islam Al-Waroqot with 51 students. This research used a case study design. Data were collected using observation, interview and documentation. Data analysis in this research was done with descriptive. The results of this research indicated that the implementation steps include the preparation of media needed, the teacher explains about pronunciation, the teacher displays pieces of video animation in power point, the teacher applies listen and repeat technique, and gives the conclusion. The challenges faced by the students namely the technical disturbances during of learning, limited vocabulary that can be learned and the classroom becomes noisy. This finding confirms that successful implementation is strongly influenced by resource readiness and learning environment support. Thus, this research provides a new perspective on the importance of careful planning and teacher training in integrating video animation in pronunciation learning process.